Використання тунельного контакту в польовому транзисторі на основі графену - Ануфрієв, В. В. (ХНУРЕ, 2021)
In a tunnelling transistor, unlike a conventional field-effect transistor the channel is controlled by the quantum tunnelling effect rather than by charge injection. The purpose of this article is to consider the design and features of a graphene-based tunnelling field-effect transistor.
Keywords: икористання тунельного контакту; транзистор на основі графену